Habitus patriarki pemilihan calon Kepala Sekolah di SMA Negeri Sumenep - Akbar Mawlana (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2023)
The schools in Sumenep still become spaces that reproduces patriarchy. Documentation data at two high schools, SMAN 1 Kalianget and SMAN 1 Sumenep, show that for 15 years the majority of teachers selected to participate in the selection of principal candidates were male teachers. This study aims to analyze the patriarchal habitus of selecting prospective principals at SMAN 1 Sumenep and SMAN 1 Kalianget. So far, the selection of school principal candidates has been a contested space that is full of conflicts, but is often forgotten. The method used is qualitative with a Schutz phenomenological approach. Interviews, observations, and documentation became tools for data collection. Through Bourdieu's theory, the result is that the reproduction of the patriarchal teacher selection to participate in the selection of prospective principals occurs due to the defeat of female teachers' accumulated capital with male teachers. In addition, there is the politicization of religion and matrilineal relations with patriarchy being the main habitus. This condition causes female teachers to experience defeat in an arena.